The contraction of the definition of beneficiary in Jersey—is it real or imagined?. Issue 1 (6th December 2022) - Hooper, Katie; Lewis, Paul
Abstract: Two recent decisions of the Royal Court of Jersey have focused attention on the nature of a beneficiary's interest under a discretionary trust in Jersey. In Kea Investments Limited v Watson, 1 the Court considered whether the interests of a discretionary beneficiary could be distrained upon pursuant to Article 10(11) of the Trusts (Jersey) Law 1984. In Patel & Ors v JTC Trust Company Limited, 2 the Master of the Royal Court considered the separate question of whether the Royal Court had the power to impound the interest of a discretionary beneficiary pursuant to Article 46 of the Trusts (Jersey) Law 1984. These decisions provoke thought as to how we must now consider the nature of a discretionary beneficiary's interest under a Jersey trust. While being separate and distinct decisions, they arguably share a common thread as they demonstrate the Royal Court indirectly adopting a contextual and/or purposive approach when construing the definition of a 'beneficiary' in the Trusts (Jersey) Law 1984, in order to meet the justice of the case.